2010
DOI: 10.1016/j.cca.2010.03.023
|View full text |Cite
|
Sign up to set email alerts
|

HDL in humans with cardiovascular disease exhibits a proteomic signature

Abstract: Background-Alterations in protein composition and oxidative damage of high-density lipoprotein (HDL) have been proposed to impair the cardioprotective properties of HDL. We tested whether relative levels of proteins in HDL 2 could be used as biomarkers for coronary artery disease (CAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 44 publications
1
70
0
1
Order By: Relevance
“…by guest, on May 12, 2018 www.jlr.org Downloaded from artery disease (CAD) ( 23,74,75 ). They identifi ed several proteins that were enriched in the CAD patients, including apoE, apoC-IV, PON1, complement C3, and apoA-IV, all involved in vascular infl ammation.…”
Section: Hdl Functional Diversity Matches Its Proteomic Diversitymentioning
confidence: 99%
“…by guest, on May 12, 2018 www.jlr.org Downloaded from artery disease (CAD) ( 23,74,75 ). They identifi ed several proteins that were enriched in the CAD patients, including apoE, apoC-IV, PON1, complement C3, and apoA-IV, all involved in vascular infl ammation.…”
Section: Hdl Functional Diversity Matches Its Proteomic Diversitymentioning
confidence: 99%
“…Some studies have reported enrichment with apoC-III in the HDL of patients with CHD (Vaisar et al 2010;Kavo et al 2012;Jensen et al 2012). Interestingly, Jensen and coworkers found that HDL particles without apoC-III were inversely associated with the risk of CHD while apoC-III-containing HDL particles were directly associated with increased risk of CHD .…”
Section: Hdl Apolipoproteinsmentioning
confidence: 99%
“…The protein content of HDL particles has been characterized recently using various methods commonly described as proteomics. It has been shown that HDL2 fraction of CHD patients carries a distinct protein cargo (Vaisar et al 2010;Gordon et al 2010;Kavo et al 2012;Alwaili et al 2012). Proteomics as a new promising approach for detecting biomarkers and mechanisms could potentially explain the beneficial characteristics of HDL particles unrelated to their cholesterol content.…”
Section: Hdl Proteomicsmentioning
confidence: 99%
“…Traditional methods, established in the 1950s (Havel et al, 1955), imply ultracentrifugation in high-salt media containing KBr or NaBr. Several lipoproteomic studies have been published using these procedures of lipoprotein isolation (Banfi et al, 2009;Davidson et al, 2009;Green et al, 2008;Heller et al, 2005Heller et al, , 2007Hortin et al, 2006;Karlsson et al, 2005aKarlsson et al, , 2005bKhovidhunkit et al, 2004;Mancone et al, 2007;Mazur et al, 2010;Rezaee et al, 2006;Vaisar et al, 2007Vaisar et al, , 2010Alwaili et al, 2011). However, the high ionic strength and the high centrifugal field forces might cause either the dissociation of proteins or their exchange between different lipoprotein classes, altering the pattern of associated exchangeable apolipoproteins.…”
Section: Lipoproteomicsmentioning
confidence: 99%
“…This analysis revealed that HDL 2 of CAD subjects carried a distinct protein cargo with increased levels of apo C-III and decreased levels of apo C-I, two apolipoproteins involved in the metabolism of HDL particles. Moreover, they found increased levels of apo A-I peptides containing oxidized methionine indicating the occurence of oxidative processes in CAD patients (Vaisar et al, 2010). Heller et al used a shotgun LC MS/MS approach to characterize HDL protein composition of 7 hypercholesterolemic subjects and 9 normolipidemic ones.…”
Section: Hdlmentioning
confidence: 99%